2018
DOI: 10.7324/jabb.2018.60102
|View full text |Cite
|
Sign up to set email alerts
|

Application of Mentha suaveolens essential oil as an antimicrobial agent in fresh turkey sausages

Abstract: The aim of this study is to evaluate the antimicrobial effect of Mentha suaveolens essential oil against pathogenic bacteria in fresh turkey sausages. The essential oil was extracted by hydrodistillation. The antibacterial activity was carried out by agar diffusion and microplates methods against Escherichia coli, Salmonella, Staphylococcus aureus, Pseudomonas aeruginosa, Klebsiella pneumonia, and Streptococcus faecalis. The antioxidant activity was carried out by ferric reducing antioxidant power and free rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Regarding the first strategy, the study carried out by Ed-Dra et al [40] explored the addition of Mentha suaveolens EO (2, 5, and 10 mg/g) as a natural preservative in fresh turkey sausages. According to authors, a reduction of 1.2 log CFU/g in E. coli after 48 h of storage at 4 • C was obtained using 10 mg EO/g.…”
Section: Meat and Meat Productsmentioning
confidence: 99%
“…Regarding the first strategy, the study carried out by Ed-Dra et al [40] explored the addition of Mentha suaveolens EO (2, 5, and 10 mg/g) as a natural preservative in fresh turkey sausages. According to authors, a reduction of 1.2 log CFU/g in E. coli after 48 h of storage at 4 • C was obtained using 10 mg EO/g.…”
Section: Meat and Meat Productsmentioning
confidence: 99%
“…The ability to convert Fe 3+ to Fe 2+ was used to assess the ferric reducing capacity of L. saligna extract, according to the previously described method [51], with few modifications. Briefly, a mixture containing 2.5 mL of phosphate buffer (0.2 M, pH 6.6) and 2.5 mL of 1% potassium ferrycyanide [K 3 Fe (CN) 6 ] was prepared and then 1 mL of each sample concentration (0.0625-2 mg/mL) was added.…”
Section: Frap Assaymentioning
confidence: 99%
“…Ferric to ferrous ion reduction was used to determine the reductive capacity of A-EO (Ed-Dra et al 2018a). Briefly, 1 mL of each concentration of A-EO was mixed with 2.5 mL of potassium hexacyanoferrate K3Fe(CN) (Ed-Dra et al 2018a) solution and 2.5 mL of phosphate buffer (0.2 mol/L, pH 7.0) and incubated at 50°C for 30 min.…”
Section: Antioxidant Activity: Ferric Reducing Antioxidant Powermentioning
confidence: 99%
“…The EOs can be defined as a complex oily mixture of various organic constituents such as terpenes, sesquiterpenes, phenolic ethers, nitrogen and sulfur compounds responsible for their biological properties (Telci et al 2006;Langeveld et al 2014). Several authors have demonstrated the antioxidant, anti-inflammatory, and anti-carcinogenic properties of different EOs that have been used against parasites, yeast, mold, and bacteria (Lu et al 2004;Viuda-Martos et al 2008;Hirota et al 2010;Giarratana et al 2014;Giarratana et al 2017;Ed-Dra et al 2018a).…”
Section: Introductionmentioning
confidence: 99%